Hubungan Obesitas dengan Kondisi Jaringan Periodontal Masyara- kat Di Wilayah Puskesmas Ranggo NTB - Sari, Ivo Maria; Sulistyani, Herastuti; Yuniarly, Etty (Journal of Oral Health Care, 2019)
Obesity and periodontal disease are chronic conditions in which prevalence tends to increase. Periodontal tissue disease is an inflammation caused by bacteria, and the process began with swelling on the gingiva until the loss of alveolar bone. To investigate the correlation between obesity and condition of periodontal tissue in the Community Health Center in Ranggo, West Nusa Tenggara. Method: This research was observational analytical with cross-sectional. This research was conducted from October-December 2018. The population of this research is obese people in Community Health Center in Ranggo. Samples were collected using purposive sampling. Data were obtained from the record of body weight and height with the Body Mass Index and the examination of periodontal tissue conditions with the Community Periodontal Index. Data were analyzed using Kendall’s tau-b. The level of obesity in the Community Health Center of Ranggo was included level II 60% with the periodontal condition in inadequate criteria 72,5%. The analysis of the correlation between obesity and the disease of periodontal tissue of the Community Health Center in Ranggo was p = 0.011. Obesity has a relationship between the condition of periodontal tissue in the Community Health Center of Ranggo, West Nusa Tenggara.